Food Insecurity of Rice in Pakistan (Global Business Management Review (GBMR), 2014)
The study of Food Insecurity of rice in Pakistan was to evaluate the impact of insecurity of rice on people of Pakistan. In Pakistan the rice stands for a situation where at one side there is rice available but on the other side the people don’t have enough accessibility of rice. The study will focus on qualitative research as this research phenomenon is comparatively new in Pakistan. Such study is rare so it is difficult to collect the data regarding the progress of Food Insecurity in Pakistan on rice. The research is based on the potential of rice and products in Pakistan related to the agriculture institutions, private representatives and government’s representatives. One of the biggest findings of this research was the gaps between realities and polices. The implementation from research will help government authorities, policy makers, market committees, traders, brokers, and exporters to understand the overall dynamics and mechanism of rice sector in Pakistan.